Non-alcoholic fatty liver disease and non-alcoholic steatohepatitis in patients with HIV. (March 2017) - Verna, Elizabeth C
Summary: Liver disease is a leading cause of morbidity and mortality among people with HIV, and in this era of safer and more effective hepatitis C therapy, non-alcoholic fatty liver disease (NAFLD) could soon emerge as the most common liver disease in this population. NAFLD is common among patients with HIV, and might be more likely to progress to non-alcoholic steatohepatitis (NASH) and NAFLD-related fibrosis or cirrhosis in these patients than in individuals without HIV. Several mechanisms of NAFLD pathogenesis are postulated to explain the disease severity in patients with HIV; these mechanisms include the influence of the gut microbiome, and also metabolic, genetic, and immunological factors. Although treatment strategies are currently based on modification of NAFLD risk factors, many new drugs are now in clinical trials, including trials specifically in patients with HIV. Thus, the identification and risk-stratification of patients with HIV and NAFLD are becoming increasingly important for accurately counselling of these patients regarding their prognosis and for establishing the most appropriate disease-altering therapy.